Eksplorasi Pandangan Gen Z Terhadap Pemanfaatan Web Digital Sebagai Media Promosi Wisata Bogoraquagame: Exploration Of Gen Z's Views On The Use Of The Digital Web As A Medium For Bogoraquagame Tourism Promotion - Nursyahbani, Muhamad Aditya; Priatna, Wahyu Budi; Dharmawan, Leonard (DAS Institute, 2025)
This study aims to explore Generation Z’s perceptions of utilizing digital web platforms as promotional media for Bogor Aquagame tourism. The rapid development of digital technology has transformed how tourists search for information and choose travel destinations, particularly among Generation Z, who are recognized as digital natives. This research employs a descriptive quantitative approach with a total sample of 31 respondents, consisting of students from the Digital Communication and Media Study Program, Class of 61. Data were collected through a Likert-scale questionnaire measuring perceptions of information accessibility, content quality, interactivity, information credibility, destination image, and visit intention. The research findings are expected to illustrate the effectiveness of digital web platforms in building the image of Bogor Aquagame and determine their influence on Generation Z’s intention to visit. This study contributes to the development of more effective and youth-oriented digital tourism promotion strategies.